Laser-Induced After-Effect in Tunnel Magnetic Nanostructures - Krupa, M.M.; Kostishin, V.G.; Korostil, A.M. (Металлофизика и новейшие технологии, 2014)
The laser-induced magnetic after-effects in magnetic nanostructures consisting in magnet reversal under ultra-short circularly polarized laser pulses are studied. Using the magneto-optical method and a pump—probe technique based on the Kerr and Faraday effects, features and conditions of magnetic reversal in ferrimagnetic-based nanostructures under femtosecond circularly polarized laser pulses are established. As shown, the mechanisms of such laser-induced impact are a complex process of laser-induced thermal demagnetization of magnetic sublattices with a subsequent magnetic biasing by internal magnetic fields of different nature. Depending on the laser-pulse duration and intensity, they can be effective magnetic fields of laser irradiation or internal magnetic fields conditioned by different rates of the thermal demagnetization of ferrimagnetic sublattices. Features of the laser-induced tunnel magnetoresistance effect in ferrimagnetic junctions are considered.